1995
DOI: 10.1111/j.1365-294x.1995.tb00198.x
|View full text |Cite
|
Sign up to set email alerts
|

Parentage analysis within a semi‐free‐ranging group of Barbary macaques Macaca sylvanus

Abstract: This study of a group of semi-free-ranging Barbary macaques Macaca sylvanus aimed to determine paternity, to establish whether any individual male achieved prominent mating success and to assess genetic variability. Analyses involved electrophoresis of 15 blood protein systems and multilocus DNA fingerprinting (isotopic and nonisotopic). Genetic variability was low; only two blood protein systems were polymorphic. Although all DNA-fingerprints were individual-specific, they showed a high average band-sharing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
(6 reference statements)
0
6
2
Order By: Relevance
“…Indeed, some authors found a positive correlation in some nonseasonal breeders: M. fascicularis (de Ruiter et al, 1994), M. arctoides (Bauers and Hearn, 1994), and M. sinica (Keane et al, 1997). By contrast, researchers did not detect a clear relationship between male rank and reproductive success in some seasonal breeders: M. fuscata (Takahata et al, 1999), M. mulatta (Berard et al, 1993), and M. sylvanus (Paul et al, 1993;von Segesser et al, 1995;and this study). However, for some of them results from different studies were inconsistent: M. mulatta (Berard et al, 1993;Smith, 1993), M. fuscata (Soltis et al, 1997(Soltis et al, , 2001) and M. fascicularis (de Ruiter et al, 1994;Shively and Smith, 1985).…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…Indeed, some authors found a positive correlation in some nonseasonal breeders: M. fascicularis (de Ruiter et al, 1994), M. arctoides (Bauers and Hearn, 1994), and M. sinica (Keane et al, 1997). By contrast, researchers did not detect a clear relationship between male rank and reproductive success in some seasonal breeders: M. fuscata (Takahata et al, 1999), M. mulatta (Berard et al, 1993), and M. sylvanus (Paul et al, 1993;von Segesser et al, 1995;and this study). However, for some of them results from different studies were inconsistent: M. mulatta (Berard et al, 1993;Smith, 1993), M. fuscata (Soltis et al, 1997(Soltis et al, , 2001) and M. fascicularis (de Ruiter et al, 1994;Shively and Smith, 1985).…”
Section: Discussioncontrasting
confidence: 38%
“…Paul et al (1993) found correlations between male rank and male reproductive success in 3 of 4 mating seasons, but only when subadult males were included in the analysis. In a different study, von Segesser et al (1995) demonstrated that out of 10 adult and subadult males at least 5 and possibly as many as 8 fathered infants. However, in that study no quantitative data on rank relationships were available.…”
Section: Introductionmentioning
confidence: 99%
“…In Gibraltar subadult and adult males between 5 and 7 years of age were the most successful, whereas males aged 10 years and above contributed to only 36% of total reproductive success. Such results have not been reported before for Macaca sylvanus and differ considerably from those found by other authors [Kuester et al, 1995;Kümmerli & Martin, 2005;Paul et al, 1993;von Segesser et al, 1995], reporting that reproductive success of males was highest at 11 years of age and above. Although Kümmerli and Martin [2005] studied the same group on Middle Hill, the authors used data before group fission in 1998, including a different set of males with a dominance structure strikingly different from that in the present population.…”
Section: Reproductive Success Of Subadult Malescontrasting
confidence: 83%
“…Previous studies of Barbary macaques focused on variation in allozymes and in minisatellite DNA fingerprints and revealed a relatively low level of genetic variation (e.g. Küster et al 1992; Ménard et al 1992; Scheffrahn et al 1993; von Segesser et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Dispersing males typically migrate over short distances, such that they usually join neighbouring social groups (Ménard & Vallet 1996). The Barbary macaque differs from most other macaque species in having a highly promiscuous mating system, such that several males achieve paternity in a group at any one time (Ménard et al 1992; von Segesser et al 1995). This will increase effective population size and thus mitigate the effects of genetic isolation.…”
Section: Introductionmentioning
confidence: 99%